Mine, yours and ours: economic analysis of Property Law - Friedman, David (2017)
In this article, the author analyzes the property legal system has to achieve efficient and useful results. In addition, he points out the reasons for the existence of private property and public property, then he explains the costs and benefits of private property, and he states the difference between real and personal property is the registry system. He concludes by stating the courts believe that a property agreement is obligatory if it is economically efficient.